Periportal fields cause stronger cooling effects than veins in hepatic microwave ablation: an in vivo porcine study. (March 2021) - Poch, Franz GM; Geyer, Beatrice; Neizert, Christina A; Gemeinhardt, Ole; Niehues, Stefan M; Vahldiek, Janis L; Frericks, Bernd; Lehmann, Kai S
Background: Vascular cooling effects are a well-known source for tumor recurrence in thermal in situ ablation techniques for hepatic malignancies. Microwave ablation (MWA) is an ablation technique to be considered in the treatment of malignant liver tumors. The impact of vascular cooling in MWA is still controversial. Purpose: To evaluate the influence of different intrahepatic vessel types, vessel sizes, and vessel-to-antenna-distances on MWA geometry in vivo. Material and Methods: Five MWAs (902–928 MHz) were performed with an energy input of 24.0 kJ in three porcine livers in vivo. MWA lesions were cut into 2-mm slices. The minimum and maximum radius of the ablation area was measured for each slice. Distances were measured from ablation center toward all adjacent hepatic vessels with a diameter of ≥1 mm and within a perimeter of 20 mm around the antenna. The respective vascular cooling effect relative to the maximum ablation radius was calculated. Results: In total, 707 vessels (489 veins, 218 portal fields) were detected; 370 (76%) hepatic veins and 185 (85%) portal fields caused a cooling effect. Portal fields resulted in higher cooling effects (37%) than hepatic veins (26%, P  < 0.01). No cooling effect could be observed in close proximity of vessels within the central ablation zone. Conclusion: Hepatic vessels influenced MWA zones and caused a distinct cooling effect. Portal fields resulted in more pronounced cooling effect than hepatic veins. No cooling effect was observed around vessels situated within the central white zone.